Lophiostomataceae (Dothideomycetes): Introducing Lophiostoma khanzada-kirgizbaeva sp. nov. and Paucispora xishanensis sp. nov. - Aluthmuhandiram, Janith V.s.; Wanasinghe, Dhanushka N.; Thilini Chethana, K.w.; Gafforov, Yusufjon; Saichana, Natsaran; Li, Xing Hong; Yan, Jiye; Mamarakhimov, Oybek M. (Phytotaxa, 2022)
Lophiostomataceae species commonly occur as saprobes on twigs, stems or bark on diverse woody and herbaceous plants in aquatic and terrestrial habitats. In the present study, we introduce Lophiostoma khanzada-kirgizbaeva sp. nov. and Paucispora xishanensis sp. nov. as new species isolated from woody substrates from Uzbekistan and China, respectively. Species delimitation was conducted using morphological and molecular phylogenetic approaches. Maximum likelihood and Bayesian inference analyses of a combined SSU, ITS, LSU, tef1-α and rpb2 sequence matrix revealed that L. khanzada-kirgizbaev and P. xishanensis are distinct from other Lophiostoma and Paucispora species in Lophiostomataceae, respectively.